2022
DOI: 10.3389/fphys.2022.1044575
|View full text |Cite
|
Sign up to set email alerts
|

Cys-loop receptors on cannabinoids: All high?

Abstract: Endocannabinoids (eCBS) are endogenously derived lipid signaling molecules that serve as tissue hormones and interact with multiple targets, mostly within the endocannabinoid system (ECS). The ECS is a highly conserved regulatory system involved in homeostatic regulation, organ formation, and immunomodulation of chordates. The term “cannabinoid” evolved from the distinctive class of plant compounds found in Cannabis sativa, an ancient herb, due to their action on CB1 and CB2 receptors. CB1/2 receptors are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 231 publications
(322 reference statements)
0
3
0
Order By: Relevance
“…Both excitatory and inhibitory synaptic transmission can be modulated by these receptors [ 66 ]. In humans, a reduction in α7-nAChR expression has been associated with an increase in seizure susceptibility [ 67 ]. α7-nAChR agonists have pro-cognitive effects, and its modulation has been proposed to be relevant for the treatment of Alzheimer’s disease (AD) or cognitive symptoms of schizophrenia, among others [ 68 ].…”
Section: Molecular Targets Reported For Cannabidiolmentioning
confidence: 99%
“…Both excitatory and inhibitory synaptic transmission can be modulated by these receptors [ 66 ]. In humans, a reduction in α7-nAChR expression has been associated with an increase in seizure susceptibility [ 67 ]. α7-nAChR agonists have pro-cognitive effects, and its modulation has been proposed to be relevant for the treatment of Alzheimer’s disease (AD) or cognitive symptoms of schizophrenia, among others [ 68 ].…”
Section: Molecular Targets Reported For Cannabidiolmentioning
confidence: 99%
“…The high concentration of cannabinoids in the flowers explains their preference, as these compounds modulate the body's homeostasis and mood by interacting with the peripheral and central nervous systems, especially with the cannabinoid-1 and cannabinoid-2 (CB1 and CB2) receptors. [33][34][35][36][37] However, some studies indicated different preferences for other plant parts. For example, Lozano et al reported a significant inclination toward the seeds, which are rich in essential fatty acids and proteins.…”
Section: Parts Of Plants Usedmentioning
confidence: 99%
“…Virtually all inhibitory functions within the CNS involve GlyRs and GABA A Rs; thus, cannabinoids’ ability to modulate these channels confers them enormous pharmacological potential and offers new therapeutic opportunities. Recently, Schmiedhofer et al conducted a comprehensive review on endo- and phytocannabinoids’ effects on cationic and anionic channels, including pharmacological aspects, and discussed cannabinoids’ possible impact as first-line treatments for epilepsy, chronic pain, and other neuropsychiatric disorders . Here, we review the advances made toward understanding the molecular determinants of cannabinoid action, starting with the first reports of phytocannabinoids’ effects on inhibitory Cys-loop channels, the establishment of their significance in THC-induced analgesia, followed by a critical revision of the different molecular models proposed over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schmiedhofer et al conducted a comprehensive review on endo-and phytocannabinoids' effects on cationic and anionic channels, including pharmacological aspects, and discussed cannabinoids' possible impact as first-line treatments for epilepsy, chronic pain, and other neuropsychiatric disorders. 31 Here, we review the advances made toward understanding the molecular determinants of cannabinoid action, starting with the first reports of phytocannabinoids' effects on inhibitory Cys-loop channels, the establishment of their significance in THC-induced analgesia, followed by a critical revision of the different molecular models proposed over the years. To conclude, we examine recent findings obtained from both the resolution of cryo-EM structures 32 and thorough computational studies on the cannabinoid binding mode, 33 comparing results, strengths, and limitations of each method.…”
Section: Introductionmentioning
confidence: 99%